Enhancing Dragon Fruit (Hylocereus undatus) Propagation Efficiency through Growing Media - Anagha, P. K.; Prakasha, D. P.; Anand, N.; Vijay, M.; Ryavalad, Shivayogi; Sree, Mude Ramya (International Journal of Economic Plants, 2025)
The experiment was carried for one and half year during November, 2019 to January, 2020 under the shade house of Fruit nursery at Main Horticultural Research and Extension Centre (MHREC), College of Horticulture, University of Horticultural Sciences, Bagalkot, Karnataka, India to assess the influence of different media on root induction, growth and shoot parameters in dragon fruit. The experiment involving different media viz., sand, sand+soil, sand+fym, sand+vermicompost, sand+soil+fym, sand+soil+vermicompost, soil, soil+fym, soil+vermicompost, fym and vermicompost was carried out using completely randomized design (CRD). It revealed that vermicompost was found the best media for the propagation of cutting which recorded early sprouting (13.2 days), highest sprout length, number of sprouts per cutting, length of the longest root, number of primary roots, fresh weight, dry weight (15.19 cm, 3.20, 15.08 cm, 9.60, 82.00 g, 34.60 g respectively at 90 days after planting), and survival percentage (84%), whereas, the sand and soil media combination resulted in the lowest performance of dragon fruit cuttings, with minimal sprout length (4.10 cm), low percentage of cuttings sprouted (24%), and poor root development (9.64 cm longest root, 3.60 primary roots) with lowest fresh weight (27.80 g), dry weight (11.80 g) and survival percentage (20%) at 90 DAP. Hence, it appears, a rooting media with more fertility would be highly useful in obtaining high root and shoot parameters in dragon fruit. The results of this study are helpful in choosing propagation media for large scale planting material.